(3eMGSHI GdefTBJ GdSjGMjI (B/s - (3GdCNQS, YGWas; (3MehOI, SejQ s ((3YeGf(B: s (3OGQ GdHQcI ddfTQ hGdJhRjY(B, s, 2001)
(3GdefTBJ GdSjGMjI, eMGSHI GdefTBJ GdSjGMjI, GdfXGe GdeMGSHj aj GdefTBJ GdSjGMjI, GdeUQhaGJ hGdEjQGOGJ, QCS GdeGd(B- (3GdeYGdLI GdeMGSHjI, GdJShjbGJ GdLQOjI, GdJObjb heYGdLI GdGNWGA GdeMGSHjI, EYOGO GdbhGFe GdeGdjIs
(3GdeQGLY U(B. 158s
Keywords: (3GdTQcGJ (B- (3GdeMGSHIs; (3GdafObIs